Guidance Services for Gifted and Talented Students in Primary Education: A Review of Effective Guidance Programs - Felly Lailatul Rahmi; Indah Oktavia (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2025)
This study aims to develop a comprehensive literature-based framework on effective guidance programs for gifted and talented children in elementary schools. Through an in-depth literature review, this study identifies the characteristics of gifted and talented children, their specific needs, and various guidance approaches that have been implemented in educational settings. The findings indicate that effective guidance programs should be tailored to students’ individual potentials and interests and should incorporate multiple components, such as mentoring, the availability of learning resources, and a supportive learning environment. Gifted and talented children at the elementary school level demonstrate unique characteristics, including high cognitive abilities and creativity, which require specialized educational and guidance approaches. Furthermore, the roles of parents, teachers, and schools are crucial in creating an optimal environment that supports the growth and development of gifted and talented children.